The Cultural Significance of the Complex of Hue Monuments: A World Heritage Gem - An Vinh Le (Engineering Research: Perspectives on Recent Advances Vol. 7, 2025)
The ancient capital city of Hue, located in central Vietnam, served as the base of the Nguyen Dynasty (1802-1945). It is home to the Complex of Hue Monuments, which was designated as the first UNESCO World Cultural Heritage site in Vietnam in December 1993, recognised for its outstanding universal value and safeguarded for the benefit of humanity. Since then, it has become a significant cultural representative of Vietnam. This paper provides an overview of the Complex of Hue Monuments, which includes the Citadel, the Imperial City, the Emperor’s Mausoleums, the Imperial Esplanade, Arenas, Pagodas, Temples, Shrines, and the surrounding natural environment. However, the site suffered significant damage during the Indochina War in the latter half of the 20th century from 1947-1975. As a result, UNESCO initiated a safeguarding campaign, leading to a series of conservation and restoration activities supported by international partners since the late 1980s. In addition, this study proposes supplementing the existing conceptual framework by introducing an intermediary notion between conservation, inheritance, and utilisation. This aims to provide a clearer roadmap for recognising the value of cultural heritage, offering a conceptual guide for conservation and contributing to the development of Vietnam. Architectural heritage conservation is not limited to the preservation of material structures alone. It also encompasses the safeguarding of all elements connected to their existence—tangible and intangible—and strives for the potential revitalisation of such heritage for the benefit of humanity. In this context, the restoration and reconstruction of significant architectural heritage sites within the Complex of Hue Monuments—especially those of outstanding universal value that have been lost, such as Can Chanh Dien Palace (to be discussed in a subsequent study)—is not only feasible but also imperative.